Mutations in the NS2B and NS3 genes affect mouse neuroinvasiveness of a Western European field strain of tick-borne encephalitis virus - Růzek, Daniel; Gritsun, Tamara S; Forrester, Naomi L; Gould, Ernest A; Kopecký, Jan; Golovchenko, Maryna; Rudenko, Nataliia; Grubhoffer, Libor (Virology, 2008)
An attenuated strain (263) of the tick-borne encephalitis virus, isolated from field ticks, was either serially subcultured, 5 times in mice, or at 40 degrees C in PS cells, producing 2 independent strains, 263-m5 and 263-TR with identical genomes; both strains exhibited increased plaque size, neuroinvasiveness and temperature-resistance. Sequencing revealed two unique amino acid substitutions, one mapping close to the catalytic site of the viral protease. These observations imply that virus adaptation from ticks to mammals occurs by selection of pre-existing virulent variants from the quasispecies population rather than by the emergence of new random mutations. The significance of these observations is discussed.
Keywords: sekvence nukleotidů; mutace; klíšťata; virové nestrukturální proteiny; virulence; Brain; Sequence Analysis, DNA; sekvenční analýza DNA; Europe; Ticks; Amino Acid Sequence; Encephalitis Viruses, Tick-Borne; Virulence; Amino Acid Substitution; molekulární modely; Mice, Inbred ICR; Selection, Genetic; Encephalitis, Tick-Borne; Evropa; Models, Molecular; selekce (genetika); Animals, Suckling; Animals; ženské pohlaví; Serine Endopeptidases; zvířata; klíšťová encefalitida; substituce aminokyselin; serinové endopeptidasy; Serial Passage; Viral Nonstructural Proteins; kojená zvířata; sekvence aminokyselin; mozek; myši; myši inbrední ICR; viry klíšťové encefalitidy; Base Sequence; Mutation; RNA-helikasy; sériové pasážování; Female; Mice; RNA Helicases